DAMPAK KINERJA KEUANGAN DALAM MEMEDIASI HUBUNGAN CORPORATE GOVERNANCE DAN NILAI PERUSAHAAN - Karina Safitri; Susi Handayani (Universitas Negeri Surabaya, 2020)
This study examines the impact of corporate governance on firm value mediated by financial performance in Indonesian state-owned companies which listed on the Indonesia Stock Exchange during the period 2011-2017. Samples were taken using a purposive sampling method. This study aims to examine the success of financial performance in mediating the relationship of corporate governance to firm value through path analysis. The findings show that the relationship of corporate governance to firm value in state-owned companies which consist of several sectors of the company was successfully mediated by ROA. This research supports the existence of signal theory explaining that all forms of information related to the company can be a signal to stakeholders.